PENGARUH JIGSAW PUZZLES GAME SEBAGAI TERAPI AKTIVITAS KELOMPOK TERHADAP KEMAMPUAN INTERAKSI SOSIAL PADA LANSIA DI DESA DUKUH KLOPO KECAMATAN PETERONGAN KABUPATEN JOMBANG - Copertino Tna’auni, Yoseph; Puspita Aryani, Hany; Dian Anggraini, Rista (LPPM STIKES HUSADA JOMBANG, 2021)
Humans naturally experience a decrease / change in their physical and psychological conditions which are interconnected with one another which is often referred to as the aging process. This situation tends to cause health problems especially in old age. The design of this research was pre-experimental with the type of one group pre-test- post-test design. The population of all elderly in the Klopo hamlet was 42 people with purposive sampling technique, with a sample size of 20 people and data collection using a questionnaire with the Wilcoxon test. The results of the study most of the respondents 'perceptions before the extension were carried out were less than 13 respondents (65%), most of the respondents' perceptions after counseling were good as many as 16 respondents (80%). The results of SPSS 16 for windows using the Wilcoxon test with a significant level of 0.05 obtained ρ = 0.000 <α (0.05), so Ho (null hypothesis) is rejected, meaning that there is an effect of jigsaw puzzles games as group activity therapy on social interaction skills in the elderly in Dukuh Klopo Village, Peterongan District, Jombang Regency. Jigsaw puzzle game is one of the effective nursing interventions to improve the client's ability to interact. Giving therapy allows clients to support each other, learn to establish interpersonal relationships, feel togetherness and can provide input on the experiences of each client, so that it will increase the ability to socialize with others around them.